2005
DOI: 10.1002/eji.200526146
|View full text |Cite
|
Sign up to set email alerts
|

The influence of natural antibody specificity on antigen immunogenicity

Abstract: The natural antibody repertoire in humans, apes and Old World primates is distinct from the repertoire of all other placental mammals, and encodes antibodies specific for the carbohydrate epitope Galα1–3Galβ1–4GlcNAc‐R (αGal). Here, we examined whether conjugating antigens to the αGal epitope can augment their immunogenicity in α(1,3)galactosyltransferase knockout mice (GT0 mice) which, like humans, produce αGal‐specific antibodies. Immunization of GT0 mice with BSA conjugated to αGal (αGal‐BSA) led to signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 48 publications
4
38
0
Order By: Relevance
“…Finally, other investigators 50 have shown that conjugating a protein antigen to a foreign sugar can lead to enhanced production of antibodies against the protein itself, without the need for adjuvant. This response was dependent on the presence of antibodies against the foreign glycan, with the resulting immune complexes apparently acting as an adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, other investigators 50 have shown that conjugating a protein antigen to a foreign sugar can lead to enhanced production of antibodies against the protein itself, without the need for adjuvant. This response was dependent on the presence of antibodies against the foreign glycan, with the resulting immune complexes apparently acting as an adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated in KO mice a Ͼ100-fold increase in the immune response to the immunizing gp120 of HIV after the carbohydrate chains of gp120 were enzymatically modified to replace sialic acid residues with ␣-gal epitopes that form immune complexes with anti-Gal (35). Similarly, BSA with coupled synthetic ␣-gal epitopes was shown to be much more immunogenic than BSA with carbohydrate epitopes that do not bind anti-Gal (60).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 143 further in vitro and in vivo validation is warranted to confirm the poten- individual T-cell repertoire specificity, in addition to antigen processing 340 may explain why some HLA binding peptide sequences do not induce T 341 cell activation in some individuals [58]. 342 It has recently been proposed that drug immunogenicity may be 343 affected by pre-existing antibodies, namely by the natural antibody 344 repertoire, although no definitive conclusions exist [59,60]. A fraction 345 of natural antibodies is conserved among different individuals [61,62].…”
mentioning
confidence: 99%